Influence of phytopreparations on rat parodont state at experimental metabolic syndrome - Dvulit, I. P. (Journal of Education, Health and Sport, 2017)
Aim: To investigate periodontoprotective action of 2 phytopreparations: husks of grapes meal and oak extract at the metabolic syndrome. Methods: The metabolic syndrome was reproduced into rats by used high fat diet, dysbiosis and introduced cytostatic. The husks of grapes meal was introduced per os in dose 500 mg/kg every days and the oak extract was introduced in dose 2 ml/kg with drink water. The duration of experiment was 38 days. The activities of enzyme were determined in gum (elastase, urease, lysozyme, catalase) and in periodontal bone (alkaline and acid phosphatases). The content of protein and hyaluronic acid were determined into gum, and the content of calcium and protein were determined into bone. Results: The levels of protein, hyaluronic acid, lysozyme, catalase were reduced into gum, but the levels of urease, elastase were increased at metabolic syndrome. The levels of alkaline phosphatase and content of calcium were reduced in bone but the level of acid phosphatase was increased at metabolic syndrome. Phytopreparations increased the levels of hyaluronic acid, lysozyme, catalase, but reduced levels of urease, elastase into gum, and the level of acid phosphatase into bone. Conclusion: Phytopreparations has periodontoprotective action at the metabolic syndrome.